Painful temporomandibular disorder, sleep bruxism, anxiety symptoms and subjective sleep quality among military firefighters with frequent episodic tension-type headache. A controlled study. - Wagner, Bianca de Araújo; Moreira, Pedro Ferreira, Filho (Arquivos de Neuro-Psiquiatria, 2018)
Objective To investigate associations of temporomandibular disorders (TMDs), bruxism, anxiety and sleep quality among military firefighters with frequent episodic tension-type headache (FETTH).Methods The sample comprised two groups (80 individuals): controls (mean age 35.2 years) and study group (mean age 38.5 years). Headache was diagnosed in accordance with the ICHD-III. The Research Diagnostic Criteria for TMDs were used to classify the TMDs; bruxism was diagnosed in accordance with the International Classification of Sleep Disorders; anxiety was classified using the Beck Anxiety Inventory; and sleep quality was assessed using the Pittsburgh Sleep Quality Index. In the statistical models, we used a significance level of 95%.Results Associations were found between participants with FETTH and TMDs (p < 0.001) and anxiety (p = 0.002).Poor quality of sleep (p = 0.687) and bruxism (p = 0.670) were not risk factors.Conclusion The study found that TMDs and anxiety among firefighters were associated with FETTH.
Keywords: tension-type headache; temporomandibular joint disorders; bruxism; surveys and questionnaires